Web and mobile based GPS trail planner - Eng, De Wei (2019)
There have been high usage of GPS features in both web and mobile applications. The four main features are location, mapping, tracking and navigation. Out of the four features, navigation comes out on top as the most frequent use. Numerous navigation applications that are out in the market allows users to enter their starting and destination coordinates. As these navigation applications mimicked how the users should navigate through a display of the route on the two-dimensional plane map, it still falls short in the interactivity of the application. GPS Trail Planner is a web-based application which includes interactivity of the application which the applications in the market fell short. It uses a JavaScript library called Hyperlapse.js to enable users to view the selected route in a 360 Hyperlapse video. The video is formed by stitching the images of Google Street View. In addition to the web-based application, the project also aims to develop the mobile-base counterpart. This helps to improve the flexibility of the application usage. The main features implemented in GPS Trail Planner are API server, visualization of the route and the flow of the Hyperlapse video. The API server handles the connection between GPS Trail Planner with the database. The visualization of route displays the Hyperlapse video of the selected route. Blur motion and additional images are added to improve the Hyperlapse video.